The Use of Traditional Chinese Medicine in Patients with Oral, Oropharynx, Nasopharynx, and Hypopharynx Cancers: A Retrospective Longitudinal Cohort Study in Taiwan. (October 2022) - Ben-Arie, Eyal; Inprasit, Chanya; Lottering, Bernice; Yip, Hei-Tung; Ho, Wen-Chao; Lee, Yu-Chen; Kao, Pei-Yu
Introduction: Given the prevalent use of tobacco and betel nut in the Taiwanese community, an increase risk of oral, oropharynx, and hypopharynx cancers (head and neck cancers) is apparent. The use of Traditional Chinese Medicine (TCM) and acupuncture is both common and conveniently accessible in Taiwan, with treatments being financially supported by the National Health Insurance (NHI). This study aims to investigate the use of TCM in head and neck cancers in Taiwan through a longitudinal cohort study. Methods: The Taiwan National Health Insurance Research Database (NHIRD) was utilized in order to conduct this study. The study populations consisted of oral, oropharynx, nasopharynx, and hypopharynx cancers (head and neck cancer) patients in 2002, which were then followed up until 2007 in regards to TCM use, until 2013 in regards to acupuncture use and until 2014 for all-cause mortality. Patients were divided into 4 groups. Common symptoms, Chinese herbs and formula used, TCM visits and 5 and 12 years all-cause mortality were analyzed. Results: The use of TCM was increased in the second to fourth-year post-diagnosis. TCM use in nasopharynx cancer patients was higher compared to other cancers. The number of TCM visits per patient was increased post-diagnosis. The findings suggest a non-significant reduction in 5 and 12 years all-cause mortality between TCM II and CON II groups. Conclusion: The use of TCM in new patients suffering from head and neck cancers was increased in close proximity to the cancer diagnosis. The relation between TCM use and mortality of head and neck cancer should be investigated through larger scale studies.